2023
DOI: 10.3399/bjgp.2022.0501
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the closure of general practices: a retrospective cross-sectional study

Abstract: Background: Two general practices close every week in the UK. Given the pressure on UK general practices, such closures are likely to persist. Yet we know little about the consequences. Closure refers to when a practice ceases to exist, merges or is taken over. Aim: Does practice funding, list size, workforce composition and quality change in surviving practices, when surrounding general practices close? Design and Setting: Cross-sectional study of English general practices, using data from 2016-20. Method: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…7 Consequences of practice closures are poorly understood, but evidence suggests that closure is associated with declining patient satisfaction, and increasing numbers of patients per GP in remaining surgeries. 60 Practice closures are also more common in socioeconomically deprived areas, risking widening existing inequities in access to care. 60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Consequences of practice closures are poorly understood, but evidence suggests that closure is associated with declining patient satisfaction, and increasing numbers of patients per GP in remaining surgeries. 60 Practice closures are also more common in socioeconomically deprived areas, risking widening existing inequities in access to care. 60 …”
Section: Resultsmentioning
confidence: 99%
“… 60 Practice closures are also more common in socioeconomically deprived areas, risking widening existing inequities in access to care. 60 …”
Section: Resultsmentioning
confidence: 99%
“…Closures of general practices in England were associated with reduced satisfaction with services in other practices that had to absorb the added strain and a fall in funding per patient, a study has found 1…”
mentioning
confidence: 99%